FOOD SAFETY IMPLEMENTATION IN FISH PROCESSING TECHNOLOGY: GENDER ROLES - Castro, Charena J. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2023)
Food safety is everybody’s concern, thus the Cebu Technological University, Cebu in collaboration with Bohol Island State University, Bohol, Philippines researchers enjoined to disseminate good manufacturing practices (GMP) and hazard analysis critical control point (HACCP) awareness to fish processors. This study aimed to implement food safety practices in fish processing and determine the gender roles in GMP and HACCP implementation in processing of fish and other fishery products. Based on descriptive statistics, the two active cooperatives of Sta. Fe, Cebu Philippines and Madridejos, Cebu, Philippines as benefeciaries, fish processors integrating the GMP and HACCP and marketing of the finished products were dominated with feminine and proper handling during purchasing of fish as raw materials were dominated by men. The Cebu Technological University with Bohol Island State University researcher’s food safety implementation were on the application of coconut water into the chilled marinade solution of bottled sardines in tomato sauce and in oil and washing the fish with chilled brine solution as pretreatment of fermenting small anchovies and dry-salted sardines.